Evaluación de borra de café como soporte en un catalizador de hierro para la remoción de fucsina básica mediante un proceso de oxidación catalítica por fase húmeda (2019)
For the degradation of Basic Fuchsin in wastewater, the use of Spent Coffee Grounds (SCG) was evaluated as a support for an iron catalyst to carry out the oxidation of this contaminant, varying the load of the active phase (2,5, 5 and 10%) and the incorporation method (wet impregnation and impregnation with ultrasound lasting 10 and 30 minutes) and maintaining the charge of coffee at 0.5 g/L. The objective is to determine the catalyst that presents the best physicochemical and catalytic properties at the moment of degrading the dye Basic Fuchsin by the Catalytic Wet Air Oxidation method (CWAO) at moderate conditions: temperature at 25°C, ambient pressure and air flow of 2 mL/min and at the same time to find the effects of using the SCG as a catalytic support.